The Global Impact of American Politics: A Scholarly Review - Embrace Gezan (Global Writing Academica Researching and Publishing, 2024)
This article delves into the comprehensive impacts of American political dynamics on the global stage, encompassing economic, security, and socio-cultural dimensions. Through an extensive review of existing literature and empirical data, this study reveals how U.S. domestic and foreign policies create ripple effects worldwide. Economically, decisions by American institutions such as the Federal Reserve influence global capital flows and exchange rates, while trade policies can disrupt international markets. In terms of security, U.S. military actions and alliances, like NATO, significantly shape global power balances and security strategies. Socially and culturally, American media, technological innovations, and educational institutions disseminate norms and values that affect societal structures globally. Furthermore, U.S. foreign policy plays a pivotal role in international relations, influencing global governance through diplomatic initiatives, foreign aid, and international treaties. Understanding these multifaceted impacts is essential for comprehending global political interactions and fostering international cooperation. This comprehensive analysis underscores the critical role of U.S. politics in shaping the global landscape across various domains.